Preliminary study on bird and mammal diversity at ecosystem restored areas in the Gunung Gede Pangrango National Park, West Java, Indonesia - Anton Ario; Iip Latipah Syaepulloh; Dede Rahmatulloh; Irvan Maulana; Supian Supian; Dedi Junaedi; Asep Yandar; Hasan Sadili; Arie Yanuar (Indonesian Journal of Applied Environmental Studies, 2020)
Since 2008, Conservation International Indonesia (CI Indonesia) has been working together with Gunung Gede Pangrango National Park (GGPNP) develop ecosystem restoration program in extended critical land area of National Park. More than 120,000 trees of 8 native species trees planted in an area of 300 hectares. Now the ecosystem has been restored and provides multiple benefits including become a new habitat for wildlife. The preliminary study on birds and mammals diversity in restored area was conducted in 2 months from April to May 2018 in Nagrak resort, GPPNP. The aim of this study is to assess the diversity on mammals and bird within ecosystem restored in the GGPNP. Birds were surveyed using point counts method, and mammals using camera trap. The results shows a total of 33 bird species of 22 families with the total number recorded 1,881 individuals. A total of 10 mammal species of 7 families were captured in the study area with a total of 623 trap days produced 113 independent photos of mammals. The species of mammals consist of Javan leopard (Panthera pardus melas), Leopard cat (Prionailurus bengalensis), Common palm-civet (Paradoxurus hermaphroditus), Small indian-civet (Viverricula indica), Javan gold-spotted mongoose (Hervestes javanicus), Muntjac (Muntiacus muntjac), Long-tiled macaque (Macaca fascicularis), Javan porcupine (Hystrix javanicus), Wild boar (Sus scrofa), and Malayan field rat (Rattus tiomanicus). The results obtained are evidence that restoring ecosystems is important not only for social and economic aspects but ecology for wildlife. The data gathered in this study will provide an important basis for future research and conservation management, and also provide support for biodiversity monitoring.Sejak tahun 2008, Conservation International Indonesia (CI Indonesia) bersama Taman Nasional Gunung Gede Pangrango (TNGGP) mengembangkan program pemulihan ekosistem di area perluasan taman nasional. Lebih dari 120.000 dari 8 jenis pohon jenis asli taman nasional telah ditanam di luasan 300 hektar. Kini kondisi area telah menjadi hutan kembali dan menyediakan berbagai jasa ekosistem termasuk menjadi habitat satwa liar. Studi pendahuluan tentang keanekaragaman jenis burung dan mamalia di area restorasi dilakukan selama 2 bulan yaitu dari bulan April hingga Mei 2018 di Resot Nagrak TNGGP. Survei burung menggunakan metode point count, sedangkan mamalia dengan menggunakan camera trap. Hasil menunjukkan sebanyak 33 jenis burung dari 22 famili dengan jumlah total tercatat 1.881 individu. Terdeteksi 10 jenis mamalia dari 7 famili di area penelitian dengan total 623 hari rekam dan menghasilkan 113 foto independen mamalia. Jenis  mamalia tersebut yaitu Macan tutul jawa (Panthera pardus melas), Kucing hutan (Prionailurus bengalensis), Musang luwak (Paradoxurus hermaphroditus), Musang rase (Viverricula indica), Garangan jawa (Hervestes javanicus), Kijang (Muntiacus muntjac), Monyet ekor panjang (Macaca fascicularis), Landak jawa (Hystrix javanicus), Babi hutan (Sus scrofa), dan Tikus belukar (Rattus tiomanicus). Hasil yang diperoleh menjadi bukti bahwa memulihkan ekosistem penting tidak hanya dalam aspek sosial dan ekonomi namun juga ekologi bagi satwa liar. Data yang dikumpulkan dalam penelitian ini akan memberikan dasar penting untuk penelitian masa depan dan manajemen konservasi, dan juga menyediakan dukungan untuk pemantauan keanekaragaman hayati.